OP07 Macrophage cell therapy causes the hepatic recruitment of host effector cells and improves structure and function in a murine model of chronic liver disease. (16th November 2010) - Thomas, J; Wojtacha, D; Pope, C; Gordon-Walker, T; Robson, A; Hartland, S; Ramachandran, P; Iredale, J; Forbes, S
Abstract : Introduction: Bone marrow (BM) cell populations have a number of roles in the development and resolution of chronic liver disease. Clinical trials of BM cell therapy have already begun. These have generally employed mixed cell populations often enriched for adult stem cells. Such cells may have a range of phenotypically diverse progeny. The identification of a defined cell type with beneficial effect will provide the basis of rational and predictable therapy. We have previously shown that macrophages are key mediators of scar remodelling. Iterative injury with carbon tetrachloride (CCl4) results in a well characterised model of murine hepatic fibrosis. Aim: We sought to determine whether bone marrow derived macrophages (BMMs) could be used as cell therapy for liver fibrosis. Method: Liver fibrosis was induced in female C57/Bl6 mice by 12 weeks i.p. carbon tetrachloride (CCl4). Macrophages were derived from the bone marrow of age-matched syngeneic mice cultured for 7 days under low adherence conditions in macrophage colony stimulating factor conditioned media. 8 weeks into the CCl4 injury protocol, mice received either 106 BMMs via the hepatic portal vein (n=8) or control medium (n=8). Serum was analysed for albumin and livers were analysed for mediators of inflammation, fibrosis and regeneration. To track donor cells, male (C57Bl/6) or transgenic green fluorescent protein+ (CBA) BMMs were delivered to strain-matched fibrotic wild type mice. Results: BMMs were 88% F4/80+/CD11b+, possessed characteristic morphologic and phenotypic features, and expressed the chemokines MCP-1, MIP-1α and MIP-2. At 12 weeks, C57Bl/6 mice receiving the macrophage injection had 32% less fibrosis (mean±SEM: 2.5±0.4 vs 3.7±0.3%, p<0.05) and higher serum albumin levels (46±2.6 vs 39.9±0.86 g/l, p=0.05). Significant improvements in fibrosis and serum albumin were also demonstrated in CBA mice. Donor macrophages transiently engrafted the scar increasing hepatic levels of macrophage (MCP-1), and neutrophil (MIP-1α, MIP-2 and KC) chemoattractants (p<0.05). This enhanced recruitment of host macrophages and neutrophils to the hepatic scar areas with associated increases in MMP-13 and MMP-9 (p<0.05). A 60% reduction in myofibroblast staining (p<0.05) followed. The early influx of host leukocytes was accompanied by a 346% increase in hepatic levels of the anti-inflammatory cytokine IL-10. Donor BMMs expressed high levels of the progenitor cell mitogen TWEAK. Macrophage recipients upregulated hepatic TWEAK by 216% with a 40% increase in the number of liver progenitor cells (p<0.05). Hepatocyte proliferation was not significantly affected. Conclusion: BMM therapy decreases fibrosis and increases regeneration improving clinically meaningful parameters of chronic liver disease in this model. The actions of the donor BMMs are amplified through paracrine signalling to numerically greater endogenous cell populations. Importantly, these effects are mediated by a single differentiated donor cell type, bringing clarity to the cause-effect relationship.